2000
DOI: 10.1161/01.cir.101.6.590
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Clopidogrel and Aspirin Versus Ticlopidine and Aspirin After the Placement of Coronary-Artery Stents

Abstract: After the placement of coronary-artery stents in unselected patients, antiplatelet therapy with aspirin and clopidogrel seems to be comparably safe and effective as aspirin and ticlopidine. Noncardiac events were significantly reduced with clopidogrel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(115 citation statements)
references
References 8 publications
3
107
0
5
Order By: Relevance
“…Tables 1 and 2 summarize the results of these studies. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] More recently, the results of the Clinical Outcomes Utilizing Revascularization and Aggressive Drug Evaluation (COURAGE) clinical trial have called into question the value of PCI in high-risk patients with confirmed CAD. This large, 50-center trial with 4.6 years of median follow-up per patient may result in a reduced use of coronary stents for secondary prevention, one of the major indications for the use of clopidogrel.…”
Section: S Ince Publication Of the Results Of The Clopidogrel Versus mentioning
confidence: 99%
See 2 more Smart Citations
“…Tables 1 and 2 summarize the results of these studies. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] More recently, the results of the Clinical Outcomes Utilizing Revascularization and Aggressive Drug Evaluation (COURAGE) clinical trial have called into question the value of PCI in high-risk patients with confirmed CAD. This large, 50-center trial with 4.6 years of median follow-up per patient may result in a reduced use of coronary stents for secondary prevention, one of the major indications for the use of clopidogrel.…”
Section: S Ince Publication Of the Results Of The Clopidogrel Versus mentioning
confidence: 99%
“…6 The combined use of aspirin and clopidogrel, however, has been demonstrated in many studies to increase the risk of bleeding (Tables 1 and 2). [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In addition, because clopidogrel requires a fairly long time to achieve peak response (3 to 7 days), 15 more recent studies have continued to evaluate the increase in loading doses of clopidogrel, from 300 mg to 600 mg to 900 mg, in an attempt to achieve maximal effects faster. 13,16,17 However, the increased loading doses also increase the risk of bleeding.…”
Section: S Ince Publication Of the Results Of The Clopidogrel Versus mentioning
confidence: 99%
See 1 more Smart Citation
“…The thienopyridines ticlopidine and clopidogrel belong to another class of drugs that block ADP-mediated platelet activation by irreversibly inhibiting the P2Y 12 receptors; these were shown to have superior efficacy, alone or combined with aspirin, than aspirin alone or aspirin plus anticoagulant therapy in preventing major cardiovascular complications [19]. The use of clopidogrel has predominated over ticlopidine due to its fewer adverse effects [20].…”
Section: Unmet Need In Antiplatelet Therapymentioning
confidence: 99%
“…Although the number of elective PCI procedures performed in Japan is increasing, there have been no studies to date that have provided clinical evidence for the efficacy and safety of antiplatelet drugs in these patient settings. Outside Japan, clopidogrel is widely used as an antiplatelet drug in patients with CAD who have undergone PCI since 3 randomized controlled studies [10][11][12] and several registries and meta-analyses [13][14][15][16][17][18] suggest that clopidogrel seems to be at least as effective as ticlopidine, and clopidogrel has fewer adverse drug reactions and is better tolerated compared to ticlopidine. In fact, a loading dose of 300 mg of clopidogrel followed by a maintenance dose of 75 mg once daily is used in this setting 19,20) and the same regimen will also be applied to Japanese patients for whom PCI is planned, regardless of whether the PCI is elective or urgent.…”
Section: A B C Dmentioning
confidence: 99%